On the Failure Rate Estimation for the Inverse Gaussian Distribution - YANG, Zhenlin (Institutional Knowledge at Singapore Management University, 2001)
Examines the inverse Gaussian failure rate based on the maximum likelihood predictive densities. Use of Monte Carlo simulation in comparing the estimators; Superiority of maximum likelihood estimators of the failure rate in bias and mean squared error; Sensitivity of the estimators.